Pengaruh Media Gambar terhadap Kemampuan Menyusun Teks Prosedur oleh Siswa Kelas VIII SMP PGRI 3 Medan - Tri Indah Prasasti (Multiverse: Open Multidisciplinary Journal, 2022)
This research aims to find out the influence of image media on the ability to compile the text of the procedure of students of class VIII PGRI 3 Medan Junior High School. The method used is the experimental method. The tool or instrument used is a test to arrange the text of the procedure in sequence and logical. Students who received treatment using image media were categorized as "very good" because 31 students (75.61%) scored 80-100. While students who received treatment without using image media were categorized as "failed" because 15 students (36.58%) scored <39. Technical analysis of data with test formula t with H0 results rejected and Ha accepted. That is, image media has a positive effect on the ability to compile procedural text by students of class VIII PGRI junior high school 3 Medan.